Parasitology: diagnostic yield of stool examination. - Senay, H (1989)
To assess the need for routinely submitting three stool samples per patient for recovery of enteric parasites, we reviewed the records of our parasitology laboratory for 1985-87 to determine the number of parasites that would not have been detected if only one or two samples had been submitted. A total of 16% of all stool samples were positive. For each sample that was positive for a parasite (index sample) a search was done for other stool samples, positive or negative, received from the same patient within 6 days of reception of the index sample. We identified 676 sets of two (276) or three (400) samples of which at least 1 was positive. A total of 93% of the enteric parasites were detected in the first sample in the two-sample sets. Among the three-sample sets 90% of the parasites were detected in the first sample, 8% in the second and 2% in the third. We recommend waiting for the result from the first stool sample rather than routinely submitting three samples for recovery of enteric parasites.